Aksi Partisipatif dalam Penyusunan dan Implementasi Kurikulum TPA untuk Meningkatkan Kualitas Pembelajaran - Hafzah Nur Humaeroh Huril; Ummi Alwiyatun Ni'mah; Niken Anggraini; Khairina Fadhillah Almajida (Universitas Negeri Gorontalo, 2026)
TPA Masjid Mulyo Basuki faced serious problems including a shortage of active teachers, the absence of study group divisions, and monotonous teaching methods, resulting in ineffective and unstructured learning processes. This study aimed to collaboratively develop and implement a TPA curriculum to improve the quality of learning. The method used was Participatory Action Research (PAR), in which researchers acted as facilitators while ustadz/ustadzah served as active agents of change throughout all stages, from problem identification and program design to implementation, evaluation, and reflection. The results show that a four-week-based curriculum with two weekly sessions was successfully developed and implemented: Tuesday sessions focused on individual Iqro'/Al-Qur'an recitation and Arabic writing practice, while Saturday sessions covered thematic activities such as calligraphy, fiqh, prophetic stories, and character education. The application of the curriculum using a small-group system based on students' reading abilities proved to create a more conducive classroom atmosphere, with students being easier to manage and more focused, and teachers better able to monitor each child's progress. This study demonstrates that a simple yet structured curriculum, combined with small-group learning, can significantly improve the effectiveness of TPA learning